2017
DOI: 10.1016/j.funbio.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the conifer needle endophyte, Phialocephala scopiformis DAOMC 229536 confirms evolutionary division within the fungal Phialocephala fortinii s.l. – Acephala appalanata species complex

Abstract: Despite the recent surge in mitochondrial (mt) genome sequencing, Kingdom Fungi remains underrepresented with respect to mtDNA. We describe the mt genome of the conifer needle endophyte, Phialocephala scopiformis DAOMC 229536 (Helotiales, Ascomycota). This strain is of interest to the Canadian forestry industry as it produces the anti-insectan compound rugulosin. Sequence was obtained from whole genome shotgun sequencing. Comparison to the only other published Phialocephala mt genome, Phialocephala subalpina, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Similarly, Zhang et al [82] observed a congruency between nuclear ribosomal RNA and mitochondrial protein-based trees to Cordyceps militaris. Our phylogeny data demonstrated that mitochondrial core genes are an alternative for determining phylogenetic relationships among rust fungi, as shown in other species of fungi and other organisms [83][84][85].…”
Section: Plos Onesupporting
confidence: 69%
“…Similarly, Zhang et al [82] observed a congruency between nuclear ribosomal RNA and mitochondrial protein-based trees to Cordyceps militaris. Our phylogeny data demonstrated that mitochondrial core genes are an alternative for determining phylogenetic relationships among rust fungi, as shown in other species of fungi and other organisms [83][84][85].…”
Section: Plos Onesupporting
confidence: 69%
“…However, there are significant differences among fungal groups in their relative nuclear-mitochondrial genome mutation rates (Sandor et al, 2018). Regardless, mitochondrial genes have been used for evolutionary studies in a variety of fungi, such as the endophytic fungus Phialocephala scopiformis (Robicheau et al, 2016), the entomopathogens Hirsutella vermicola (Zhang Y.-J. et al, 2017), Pochonia chlamydosporia (Lin et al, 2015), and H. thompsonii (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the fungal mitogenome project 33 , 347 fungal mitogenomes have been released in the NCBI Organelle Genome Database, 220 of which have been curated 28 . These fungal mitogenomes vary extensively in size and range from 12 kb to over 235 kb 27 ; this variation is mainly caused by intronic and plasmid-derived regions 34 .…”
Section: Discussionmentioning
confidence: 99%